If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-5n + 1) = 147 Reorder the terms: 7(1 + -5n) = 147 (1 * 7 + -5n * 7) = 147 (7 + -35n) = 147 Solving 7 + -35n = 147 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -35n = 147 + -7 Combine like terms: 7 + -7 = 0 0 + -35n = 147 + -7 -35n = 147 + -7 Combine like terms: 147 + -7 = 140 -35n = 140 Divide each side by '-35'. n = -4 Simplifying n = -4
| 5*(E-8)+4E=122 | | 19+13x=36 | | 36=-2(m+5)+m | | 1.6+0.4= | | 16x+147=419 | | 4*(D+5)-D=65 | | -8m-11=105 | | sqrt(14x-7)-3=x | | (2x-3)(x+4)=21(x-2) | | -8-3=3x+6-2x | | 4x-18=24-2x | | 10n-8-4n=14 | | -38+7x=-5(-7x+2) | | 11-17=-6X | | 48-32y= | | 10n-8=14 | | 2*(B+6)+5B=40 | | 5x+6(-2x-17)=-172 | | 8(9-z)=z | | 3u^2-4u-15=0 | | 2s-k=11fork | | 8E+9-3E=69 | | 9-12x=x | | 9-12x=x | | 9-12x=x | | -3n+7=-14 | | -1+3(-4n+6)=-2(-7n-5)-3 | | 9D-5-5D=23 | | 4abcde*20a^2b^3= | | -12+-3=-36 | | 13n-13=(-12) | | 4+2(x-3)=2[4-6(x+2)] |